2016
DOI: 10.5352/jls.2016.26.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nox4 in Neuronal Differentiation of Mouse Subventricular Zone Neural Stem Cells

Abstract: Reactive oxygen species (ROS), at appropriate concentrations, mediate various normal cellular functions, including defense against pathogens, signal transduction, cellular growth, and gene expression. A recent study demonstrated that ROS and ROS-generating NADPH oxidase (Nox) are important in self-renewal and neuronal differentiation of subventricular zone (SVZ) neural stem cells in adult mouse brains. In this study, we found that endogenous ROS were detected in SVZ neural stem cells cultured from postnatal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…It is well established that the redox signaling is essential during neurodevelopment since the transition from neural stem cells (NSC) to a neuron involves a metabolic shift from a glycolytic to a more oxidative based metabolism, which consequently increases the amount of mitochondrial-derived reactive oxygen species (ROS) [ 64 , 65 ]. Moreover, other sources of ROS, such as the NADPH-oxidase enzyme family, have also been proposed to play particularly important roles in inducing the neurogenic process [ 66 , 67 , 68 ]. Consequently, such an increase in the ROS induces the activation of several signaling cascades involved in the commitment of the NSC and its differentiation into a fully grown neuron [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that the redox signaling is essential during neurodevelopment since the transition from neural stem cells (NSC) to a neuron involves a metabolic shift from a glycolytic to a more oxidative based metabolism, which consequently increases the amount of mitochondrial-derived reactive oxygen species (ROS) [ 64 , 65 ]. Moreover, other sources of ROS, such as the NADPH-oxidase enzyme family, have also been proposed to play particularly important roles in inducing the neurogenic process [ 66 , 67 , 68 ]. Consequently, such an increase in the ROS induces the activation of several signaling cascades involved in the commitment of the NSC and its differentiation into a fully grown neuron [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the transient increase in ROS is essential to induce the commitment of the NSC, such a process needs to be tightly regulated to maintain a physiological and tolerable intracellular level of reactive species [ 72 ]. On one hand, persistent and particularly high amounts of ROS, which exceed a physiologically acceptable range, can induce oxidative stress, hinder axonal growth, and impair neurodevelopment, while on the other hand, low ROS amounts have been linked to the maintenance of the quiescent state of the NSC, which reduces its differentiation into neurons [ 67 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…A VersaMax microplate reader was used for quantitative analysis of the cell viability. WST-8 Cell Viability Assay Kit was purchased from Quanti-Max, and N5 medium was prepared in advance according to a previous report . Phosphate-buffered saline (PBS) was purchased from GenDEPOT.…”
Section: Methodsmentioning
confidence: 99%
“…NOXs, together with the mitochondria electron-transport chain, are the main intracellular sources of ROS [ 15 ]. However, ROS generated in mitochondria are a byproducts of cellular respiration meanwhile NOXs deliberately produce ROS, and this production is tightly regulated by the cell [ 16 ]. Three major forms of intracellular ROS exist: superoxide anions (O − ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (OH − ) [ 17 ].…”
Section: Noxs and Ros: Effectors And Modulators Of Redox And Metabolic Homeostasis In Stem Cellsmentioning
confidence: 99%
“…The up-regulation of NOX4 represents a mechanism to modulate different cellular processes since H 2 O 2 produced by NOX4 regulates intracellular signaling [ 146 , 147 ]. Park et al [ 16 ] observed that NOX4 was predominantly expressed among NOX isoforms in SVZ NSCs cultured from mouse neonates and its expression increased during neuronal differentiation. In addition, the treatment of SVZ NSC cultures with the antioxidant N-acetyl cysteine (NAC) reduced neurogenesis as well as the knockdown of NOX4.…”
Section: Nox Expression In Neural Stem Cells: Role In the Development And Regenerative Capacitymentioning
confidence: 99%